Biologically Structured Water-A Review (Part 2): Redox Biology, Plant Resilience, SW Drinking Water Types, BSW Water and Aging, BSW Water and Immunity - Ramsey, Craig L. (Journal of Basic & Applied Sciences, 2023)
A review was conducted between redox biology and BSW water to link their interactions with cell bioenergetics. The exchange of electrons and protons from energized BSW water significantly contributes to recycling energy biomolecules during aerobic respiration. Plant resilience to biotic and abiotic stressors is also significantly improved by maintaining adequate levels of BSW water. The physicochemical properties of SW water are readily measured and are associated with improved human health. Natural healing water and SW water products have similar physicochemical properties. Medical literature shows a direct association between dehydration and age-related diseases. Drinking SW water enhances rehydration rates and increases intracellular water content. Research has also suggested that drinking SW water has a positive effect on certain neurological diseases and cancer types. Finally, drinking SW water improves the immunity system in humans.